Inflation, price dispersion and the informational content of prices: evidence from a hyperinflation episode - Angelis, Thiago Coraucci de (2012)
This study examines the relationship between in ation and price dispersion during the hyperin ationary episode in Brazil. We look at micro data on price dynamics through the perspective of dispersion at the store level, building on the informational consequences of high price dispersion. Rather than focus on which theoretical framework best explains the relative price variability seen on the data, we focus on a top-down approach to the information embedded in prices: we analyze price setting behavior from the perspective of economic segments as whole and from the perspective of each seller taken individually. In the former case we seek to answer the following: do higher levels of in ation favor higher price dispersion? In the latter, we focus on the time-series properties of each of more than 150 real price trajectories in both high and low in ation periods. We provide further empirical evidence of the loss of information embedded in prices, be it deriving from greater overall dispersion or from a greater volatility in each seller\'s price trajectory relative to its peers\'. Our findings extend previous results, accounting for a higher level of in ation, a longer time span and a broader selection of items.